Labour market integration of immigrants in the greek labour market - Kosmas, Petros C. (My University, 2010)
This empirical study analyzes the labor market integration of immigrants in Greece. In the first stage, a descriptive analysis was conducted on the personal and occupational characteristics of both immigrants and native (Greek) employees, along with a basic comparison of wage inequality. Subsequently, three wage equations were estimated based on a partial selection of samples, in line with the human capital theory. In the second stage, wage differentials between native and immigrant workers were examined. Borjas (1999) describes economic integration as a process of accumulating human capital, which in turn narrows the wage gap between natives and immigrants. Accordingly, the wage disparities were analyzed through key determining factors. Using the Oaxaca and Ransom (1994) methodology, the study assesses interpretive variation by evaluating wage differences, including the unexplained wage gap that gives rise to economic advantages for natives and disadvantages for immigrants. Analysis based on data from the Survey of Income and Living Conditions (EU-SILC), conducted by the National Statistical Service of Greece, reveals that the assimilation process varies significantly across ethnic groups within the Greek labor market. Immigrants, in particular, display high levels of occupational instability and mobility. Wages for both natives and immigrants are shaped by individual as well as societal factors. A high concentration of immigrants in a limited range of professions inevitably drives down wage levels for both groups. The third key issue identified is that the existing wage gap stems, in part, from labor market discrimination. Technical analysis using the Oaxaca and Ransom approach indicates that mechanisms within the Greek labor market contribute to discrimination against immigrants. Specifically, 46.7% of the average wage gap cannot be explained by differences in productive characteristics. The economic advantage for native workers is estimated at 19.9%, while the corresponding disadvantage for immigrants is 26.8%. The findings of this study may serve as a valuable resource in shaping immigration policies aimed at fostering the smoother integration of immigrants into the Greek labor market.
Keywords: Labour Economics